Comprehensive numerical study of the Adelaide Jet in Hot-Coflow burner by means of RANS and detailed chemistry. (15th November 2017) - Li, Zhiyi; Cuoci, Alberto; Sadiki, Amsini; Parente, Alessandro
Abstract: The present paper shows an in-depth numerical characterisation of the Jet in Hot Co-flow (JHC) configuration using the Reynolds Averaged Navier-Stokes (RANS) modelling with detailed chemistry. The JHC burner emulates the MILD combustion by means of a hot and diluted co-flow and high speed injection. The current investigation focuses on the effect of turbulent combustion models, turbulence model parameters, boundary conditions, multi-component molecular diffusion and kinetic mechanisms on the results. Results show that the approaches used to model the reaction fine structures, namely as Perfectly Stirred Reactors (PSR) or Plug Flow Reactors (PFR), do not have a major impact on the results. Similarly, increasing the complexity of the kinetic mechanism does not lead to major improvements on the numerical predictions. On the other hand, the inclusion of multi-component molecular diffusion helps increasing the prediction accuracy. Three different Eddy Dissipation Concept (EDC) model formulations are compared, showing their interaction with the choice of the C 1 ε constant in the k − ε turbulence model. Finally, two approaches are benchmarked for turbulence-chemistry interactions, the EDC model and the Partially Stirred Reactor (PaSR) model. Highlights: A numerical investigation of novel combustion regimes is presented. A comprehensive analysis on modelling strategies in MILD combustion is carried out. The EDC and PaSR combustion models are adopted and compared. The interplay between the combustion model and the turbulence model is shown. The role of boundary conditions, turbulence model parameters is discussed.